PENGARUH MEDIA POP UP BOOK TERHADAP KEMAMPUAN MEMBACA SISWA KELAS V SDK NANGALIMANG - Yosefa Selestina; Hermus Hero; Mario Florentino (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low reading ability of fifth-grade students at SDK Nangalimang, as indicated by their lack of interest in reading, difficulties in reading, and the use of less engaging learning media. The purpose of this study was to determine the effect of pop-up book media on the reading ability of fifth-grade students at SDK Nangalimang. This research employed a quantitative approach using a one-group pretest-posttest design. The subjects of this study were all 15 fifth-grade students of SDK Nangalimang. Data were collected through reading ability tests administered before and after the treatment, as well as observation sheets of teacher and student activities. The data were statistically analyzed using a paired sample t-test with the assistance of SPSS software. The results showed that the mean pretest score was 64.33, which significantly increased to 88.66 in the posttest. The hypothesis testing yielded a t-value of -24.000 with a significance value (Sig. 2-tailed) of 0.001. Since the significance value of 0.001 was lower than 0.05, H₀ was rejected and Hₐ was accepted. Therefore, it can be concluded that the use of pop-up book media had a significant effect on the reading ability of fifth-grade students at SDK Nangalimang.